Childhood circumstances and mode of delivery - Teixeira, Cristina (2011)
Objective To assess the influence of social circumstances at 12 yrs on c-section delivery. Methods Women (n¼6827) were consecutively recruited during the assembling of a birth-cohort. Interviews were used to obtain data on social and demographic characteristics and current pregnancy events. Financial childhood circumstances were classified as low (LF) or high (HF) based on the number of amenities reported. Parents’ education was defined as low (#6 years, LPE) and high (HPE). The effect of participants’ financial socioeconomic conditions on csection risk was computed using logistic regression stratified by parents ‘education. Methods Women (n=6827) were consecutively recruited during the assembling of a birth-cohort. Interviews were used to obtain data on social and demographic characteristics and current pregnancy events. Financial childhood circumstances were classified as low (LF) or high (HF) based on the number of amenities reported. Parents' education was defined as low (≤6 years, LPE) and high (HPE). The effect of participants' financial socioeconomic conditions on c-section risk was computed using logistic regression stratified by parents ‘education. Results Women with both high financial and educational childhood circumstances were significantly older, more educated and more frequently primiparous, with normal or underweight and reporting private antenatal care. The overall c-section rate was 35.6% varying from 32.2% (LF-LE) to 41.3% (HF-HE). After adjustment and considering women in LF-LPE as reference, we obtained OR=0.92; 95% CI 0.66 to 1.28 for LF-HPE group, OR=1.19; 95% CI 1.04 to 1.37 for HF-LPE group and OR=1.38; 95% CI 1.16 to 1.64) for HF-HPE group. Stratifying by parents' education and compared with women in LF group, those in HF group showed higher risk of c-section either in the LPE group (OR=1.19; 95% CI 1.04 to 1.37) or in the HPE group (OR=1.42; 95% CI 0.99 to 2.02). Conclusions Our results suggest that, independently of the parents' education and the current socio-demographic conditions, the childhood financial environment may influence the mode of delivery.